Synthesis of novel N‐substitutedphenyl‐6‐oxo‐3‐phenylpyridazine derivatives as cyclooxygenase‐2 inhibitors. Issue 5 (16th March 2020) - Khan, Abida; Diwan, Anupama; Thabet, Hamdy K; Imran, Mohd
Abstract: Some novel non‐ulcerogenic N‐substitutedphenyl‐6‐oxo‐3‐phenylpyridazines as COX‐2 inhibitors have been developed (Supplementary material Appendix 1 ). The novel aldehyde 3 was prepared by reacting 6‐phenylpyridazin‐3(2 H )‐one with 4‐fluorobenzaldehyde. The aldehyde 3 was reacted with different hydrazines and thiazolidin‐4‐ones to obtain the novel N‐substitutedphenyl‐6‐oxo‐3‐phenylpyridazine derivatives. These were assessed for their anti‐inflammatory potential and gastric ulcerogenic effects. The molecular docking investigations were also undertaken. The spectroscopic data were coherent with the allocated structures of the compounds. The compounds 4a (IC50 = 17.45 nm; p < .05), 4b (IC50 = 17.40 nm; p < .05), 5a (IC50 = 16.76 nm; p < .05), and 10 (IC50 = 17.15 nm; p < .05) displayed better COX‐2 inhibitory activity than celecoxib (IC50 = 17.79 nm; p < .05). These findings were consistent with the molecular docking investigations of 4a, 4b, 5a, and 10 . The in vivo anti‐inflammatory profile of 4a, 4b, 5a, and 10 was also superior to celecoxib and indomethacin. The compounds 4b, 5a, and 10 revealed no gastric ulcerogenic effects, wherein the compound 4a produced almost negligible gastric ulcerogenic effects than celecoxib and indomethacin. The compounds 4a, 4b, 5a, and 10 have been postulated as promising non‐ulcerogenic COX‐2 inhibitors.